上皮细胞间质化与肿瘤的转移 (Zhongguo Fei Ai Za Zhi, 2011)
Metastasis is the transfer of malignant tumors from one organ to a distant organ. It is the most common cause of death in cancer patients. Different molecular mechanisms enable tumor cells to infltrate the surrounding tissue, invade blood vessels and leave the blood stream at a different site. Epithelial-mesenchymal transition (EMT) is critical for appropriate embryonic development, and this process is re-engaged in adults during wound healing, tissue regeneration, organ fbrosis, and cancer progression. EMT is the frst step in tumor invasion and metastasis. A detailed knowledge of the molecular requirements for EMT in human cancer will help us to beter understand tumor progression and to delineate more effective strategies for future therapeutic intervention.